Progestin-based pharmacotherapy in fertility preservation in early endometrial cancer - Qin, Zhendong; Zhang, Di; Cao, Guangming (Frontiers in Oncology, 2024)
Endometrial cancer is a common tumor of the female reproductive system. In recent years, as the age of onset of the disease has gradually become younger, this has caused distress to some young patients with reproductive needs, and the active search for methods of preserving reproductive function has gradually attracted attention. In this paper, we will systematize the current status of progestin-based pharmacotherapy in combination with other drug therapies in the conservative management of early-stage endometrial cancer. With the expectation of providing a reference for the treatment of early stage endometrial cancer patients in China and for the in-depth development of related research in this field.